PENGEMBANGAN MODEL LATIHAN BERMAIN TARGET PADA TEKNIK DASAR JUMP SERVICE PERMAINAN BOLA VOLI - Aisah R Pomatahu (Universitas Negeri Gorontalo, 2025)
This study aims to develop a target-based training model to enhance students' fundamental skills in executing the jump service in volleyball. The primary issue identified is the low level of accuracy and consistency demonstrated by students when performing the jump service, which consequently undermines the effectiveness of initial attacks during matches. The research employs a Research and Development (RD) methodology using the ADDIE model framework, which encompasses the stages of Analysis, Design, Development, Implementation, and Evaluation. The training model is constructed around engaging and competitive target-based games, such as Hit the Target, Score Zone, and Time Challenge. The participants in this study were students from SMA Negeri 1 Kota Gorontalo. Validation was conducted by two instructional design experts and one game expert, yielding an average feasibility score of 86.11%, which falls within the “highly feasible” category. A small-scale trial revealed a positive student response, with an average approval rate of 91%, indicating the model’s effectiveness in enhancing accuracy, power, and motivation in performing the jump service. The findings suggest that the target-based training model presents an innovative and effective alternative for teaching the jump service technique in secondary school volleyball education.